Endosonography - Hawes, Robert H.; Fockens, Paul; Varadarajulu, Shyam (ClinicalKey., 2015)
From diagnostic to therapeutic procedures, Endosonography, 3rd Edition is an easy-to-access, highly visual guide covering everything you need to effectively perform EUS, interpret your findings, diagnose accurately, and choose the best treatment course. World-renowned endosonographers help beginners apply endosonography in staging cancers, evaluating chronic pancreatitis, and studying bile duct abnormalities and submucosal lesions. Practicing endosonographers can learn cutting-edge techniques for performing therapeutic interventions such as drainage of pancreatic pseudocysts and EUS-guided anti-tumor therapy. Meticulous updates, electronic access to the fully searchable text, videos detailing various methods and procedures-and more-equip you with a complete overview of all aspects of EUS. Get a clear overview of everything you need to know to establish an endoscopic practice, from what equipment to buy to providing effective cytopathology services.